Lymphatic Endothelial Cell Activation and Dendritic Cell Transmigration Is Modified by Genetic Deletion of Clever-1 - Tadayon, Sina; Dunkel, Johannes; Takeda, Akira; Eichin, Dominik; Virtakoivu, Reetta; Elima, Kati; Jalkanen, Sirpa; Hollmén, Maija (Frontiers in Immunology, 2021)
Clever-1 also known as Stabilin-1 and FEEL-1 is a scavenger molecule expressed on a subpopulation of anti-inflammatory macrophages and lymphatic endothelial cells (LECs). However, its role in regulating dendritic cell (DC) trafficking and subsequent effects on immunity have remained unexplored. In this study, we demonstrate that DC trafficking from the skin into the draining lymph nodes is compromised in the absence of Clever-1. By adoptive transfer approaches we further show that the poor trafficking is due to the impaired entrance of DCs into afferent lymphatics. Despite this, injections of ovalbumin-loaded DCs into the footpads induced a stronger proliferative response of OT II T cells in the draining lymph nodes. This could be explained by the increased MHC II expression on DCs and a less tolerogenic phenotype of LECs in lymph nodes of Clever-1 knockout mice. Thus, although fewer DCs reach the nodes, they are more active in creating antigen-specific immune responses. This suggests that the DCs migrating to the draining lymph node within Clever-1 positive lymphatics experience immunosuppressive interactions with LECs. In conclusion, besides being a trafficking molecule on lymphatic vasculature Clever-1 is immunosuppressive towards migrating DCs and thus, regulates the magnitude of immune responses created by incoming DCs in the draining lymph nodes.